Tax Ethics and Professionalism in Accounting: A Systematic Literature Review - Indah Yani; Leny Marlina, Fitria Romadlona (STIE AMKOP, 2026)
Tax ethics has become a crucial issue in the accounting profession amid increasing regulatory pressure and the complexity of global taxation. This study aims to identify trends, thematic focuses, and methodological approaches in tax ethics research through a systematic literature review. 101 Scopus-indexed articles published between 2011 and 2023 were analyzed using co-word analysis with VOSviewer. The study covered 27 countries, applied 78 theories, and was published in 45 journals. Three main groups emerged: tax compliance and ethics, organizational pressure and decision-making, and ethics education. Moral and behavioral approaches dominate the literature, reflecting the multidimensional nature of tax ethics. The prominence of tax compliance and ethics highlights growing concerns about the ethical boundaries of tax planning amid increasing scrutiny of tax avoidance. This research contributes by mapping the intellectual structure of tax ethics research and emphasizing the need for contextual ethics education to strengthen accounting professionalism. Future research is encouraged to explore the role of digitalization, AI, and cross-cultural factors in shaping ethical tax behavior and professional judgment. Keywords: Ethics, Taxation, Accounting Profession, Ethics Education ,